PEMERINTAHAN BERBASIS DATA: MENGOPTIMALKAN PEMANFAATAN BIG DATA UNTUK KEBIJAKAN PUBLIK - Loso Judijanto; Reihan Putri (CV. Adiba Aisha Amira, 2024)
Data-driven government has emerged as a new paradigm in public administration, offering significant potential to improve the efficiency and effectiveness of government policies. This study examines the role of Big Data in the transformation of governance, with a focus on optimising its use for decision-making and the implementation of public policy. Through an analysis of current literature and case studies from various countries, this study identifies the main benefits of implementing Big Data in government, including improved prediction accuracy, personalisation of public services, and increased transparency. However, challenges such as data privacy, information security, and the digital divide are also critically discussed. The study concludes that despite the obstacles, the integration of Big Data in government processes has great potential to increase the government's responsiveness and accountability to the needs of the community. Recommendations for effective implementation include the development of a comprehensive regulatory framework, investment in digital infrastructure, and increased data literacy among policymakers and the general public.